Tetramethylpyrazine alleviates diabetic nephropathy through the activation of Akt signalling pathway in rats - Rai U.; Kosuru R.; Prakash S.; Tiwari V.; Singh S. (My University, 2025)
In the whole world, the principal cause of end-stage renal disease is diabetic nephropathy (DN), which is one of the most relentless complications of diabetes. However, there is a shortfall of compelling DN treatments and the mechanism potentially able to alleviate renal injury remains ambiguous. In this experiment, we estimated the preventive actions of tetramethylpyrazine (TMP) on DN in rats and further investigated the underlying mechanism. The different doses of TMP (100 mg/kg, 150 mg/kg and 200 mg/kg) were orally given each day for 8 weeks in streptozotocin (STZ) - nicotinamide (NCT) - induced type-2 diabetic (T2D) rats. The metabolic parameters of diabetes, blood urea nitrogen (BUN), serum creatinine (SCR), urinary protein and oxidative stress parameters were assessed. Microstructural changes in kidney were observed, and the expression of Akt signalling pathway proteins was measured by western blotting. TMP administration in T2D rats improved diabetic condition, as demonstrated by significant (P < 0.05) increase of body weight and fasting serum insulin (FSI) level, reduction of fasting blood glucose (FBG) and glycosylated haemoglobin (HbA1c) level and regulation of lipid profile and oral glucose tolerance in a dose-dependent manner. TMP treatment also reduced BUN, SCR, urinary protein and oxidative stress and prevented renal injury in diabetic rats. TMP activated Akt signalling pathway, increased the levels of p-Akt and Bcl-2, and diminished the expressions of p-GSK-3β, Bax and cleaved caspase-3. In conclusion, TMP ameliorates diabetic nephropathy in T2D rats by initiating the Akt signalling, improving the metabolic markers of diabetes and suppressing oxidative stress. © 2019 Elsevier B.V.